2018
DOI: 10.1016/j.ihj.2017.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Intracoronary tenecteplase in STEMI with massive thrombus

Abstract: Primary percutaneous coronary intervention is the current standard of care in ST elevation myocardial infarction (STEMI). However, large thrombus is an independent predictor for stent thrombosis and major adverse cardiac events in patients undergoing primary angioplasty for STEMI. Here we report a series of STEMI patients with large thrombus burden treated successfully with low dose intracoronary thrombolysis. There was prompt and early ST resolution. There was improvement in thrombolysis in myocardial infarct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…In our study, significant improvements in epicardial (cTFC) and myocardial (MBG) coronaryflow were found with the use of low dose intracoronary alteplase. Using different intracoronary thrombolytics, Sezer, et al [12] (using streptokinase) Boscarelli, et al, [13] (using alteplase and tenectplase) and Jayagopal and Sarjun-Basha, [14] (using tenectplase) found the same results. More physiologically, Sezer, et al [12] found that coronary flow reserve, index of microvascular resistance and Pressure derived collateral flow index were significantly lower in alteplase group.…”
Section: Acute Effects Of Intracoronary Alteplase Infusionmentioning
confidence: 81%
See 1 more Smart Citation
“…In our study, significant improvements in epicardial (cTFC) and myocardial (MBG) coronaryflow were found with the use of low dose intracoronary alteplase. Using different intracoronary thrombolytics, Sezer, et al [12] (using streptokinase) Boscarelli, et al, [13] (using alteplase and tenectplase) and Jayagopal and Sarjun-Basha, [14] (using tenectplase) found the same results. More physiologically, Sezer, et al [12] found that coronary flow reserve, index of microvascular resistance and Pressure derived collateral flow index were significantly lower in alteplase group.…”
Section: Acute Effects Of Intracoronary Alteplase Infusionmentioning
confidence: 81%
“…The use of intra-coronary thrombolysis (e.g. Alteplase) immediately after PPCI was tested and showed improved epicardial and microvascular coronary flow [12][13][14].…”
mentioning
confidence: 99%
“…11 Jayagopal Basha recently published a series of nine cases where IC tenecteplase was used successfully in patients with very high thrombus burden. 14 In the series, TNK was given IC at one fifth the systemic dose and the remaining four fifths were given systemically along with intravenous unfractionated heparin. All the patients had prompt and complete ST resolution and improvement in their TIMI myocardial blush grade with no patients having any significant bleeding.…”
Section: Discussionmentioning
confidence: 99%